Continent-Scale Sampling Reveals Fine-Scale Turnover in a Beneficial Bug Symbiont - Ravenscraft, Alison; Thairu, Margaret W.; Hansen, Allison K.; Hunter, Martha S. (Frontiers in Microbiology, 2020)
Many members of animal-associated microbial communities, including the gut flora, are acquired from their host’s environment. While many of these communities are species rich, some true bugs (Hemiptera) in the superfamilies Lygaeioidea and Coreioidea allow only ingested Burkholderia to colonize and reproduce in a large portion of the midgut. We studied the spatial structuring of Burkholderia associated with a widespread omnivorous bug genus, Jalysus (Berytidae). We sampled Wickham’s stilt bug, Jalysus wickhami, across the USA and performed limited sampling of its sister species, the spined stilt bug Jalysus spinosus. We asked: (1) What Burkholderia strains are hosted by Jalysus at different locations? (2) Does host insect species, host plant species, or location influence the strain these insects acquire? (3) How does Burkholderia affect the development and reproductive fitness of J. wickhami? We found: (1) Sixty-one Burkholderia strains were present across a sample of 352 individuals, but one strain dominated, accounting for almost half of all symbiont reads. Most strains were closely related to other hemipteran Burkholderia symbionts. (2) Many individuals hosted more than one strain of Burkholderia. (3) J. wickhami and J. spinosus did not differ in the strains they hosted. (4) Insects that fed on different plant species tended to host different Burkholderia, but this accounted for only 4% of the variation in strains hosted. In contrast, the location at which an insect was collected explained 27% of the variation in symbiont strains. (5) Burkholderia confers important fitness benefits to J. wickhami. In laboratory experiments, aposymbiotic (Burkholderia-free) insects developed more slowly and laid fewer eggs than symbiotic (Burkholderia-colonized) insects. (6) In the lab, nymphs sometimes acquired Burkholderia via indirect exposure to adults, indicating that horizontal symbiont transmission can occur via adult insect-mediated enrichment of Burkholderia in the local environment– a phenomenon not previously reported in bug-Burkholderia relationships. Taken together, the results suggest that for these bugs, critical nutritional requirements are outsourced to a highly diverse and spatially structured collection of Burkholderia strains acquired from the environment and, occasionally, from conspecific adults.